Cultural Heritage and Collective Intellectual Property Rights - Santilli, Juliana (World Bank, Washington, DC, 2012)
The inventive and creative processes of communities are often collective and the use of information, ideas and resources generated on the basis of such collective processes are broadly shared. Therefore, the concept of property rights belonging to one or more identifiable individuals is alien and contrary to the values and concepts of such societies and its adoption could foster a dissociation of knowledge from the context in which it is produced and shared. A legal regime for 'collective intellectual property rights' would avoid these difficulties. The Brazilian Federal Constitution made great progress in the protection of cultural heritage by announcing a modern inclusive and democratic legal concept. The text clearly extends the notion of cultural heritage, appreciates cultural pluralism and demonstrates a spirit of democratization of cultural policies.